2023
DOI: 10.3390/genes14040880
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Genetic Epidemiology with a Refined Targeted Gene Panel for Hereditary Hearing Impairment in the Taiwanese Population

Abstract: Hearing impairment is one of the most common sensory disorders in children, and targeted next-generation sequencing (NGS)-based genetic examinations can assist in its prognostication and management. In 2020, we developed a simplified 30-gene NGS panel from the original 214-gene NGS version based on Taiwanese genetic epidemiology data to increase the accessibility of NGS-based examinations. In this study, we evaluated the diagnostic performance of the 30-gene NGS panel and compared it with that of the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The diagnostic rate was the highest in the congenital/earlyonset group (42.9%), followed by the juvenile/young adult-onset group (31.7%), and the middle-aged/aged-onset group (21.4%). A negative correlation was also observed between the age of onset (or awareness) and diagnostic yield in previous papers [8][9][10][11]45]. These findings emphasize that a genetic etiology is involved to a considerable degree even in patients with late-onset HL.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The diagnostic rate was the highest in the congenital/earlyonset group (42.9%), followed by the juvenile/young adult-onset group (31.7%), and the middle-aged/aged-onset group (21.4%). A negative correlation was also observed between the age of onset (or awareness) and diagnostic yield in previous papers [8][9][10][11]45]. These findings emphasize that a genetic etiology is involved to a considerable degree even in patients with late-onset HL.…”
Section: Discussionsupporting
confidence: 70%
“…It was previously thought that the involvement of genetic factors is limited in late-onset HL. However, recent studies have indicated that a certain proportion of HL that presents after juvenile-onset HL or young adult-onset HL is also due to genetic causes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%